Penggunaan Metafora Visual Dalam Video Iklan Layanan Masyarakat Kick It Out - Winata Faturahman (Rekam: Jurnal Fotografi, Televisi, Animasi)
Football fans riot in Indonesia are common and many lives. Excessive negative and tends to be one of the causes frequent riots between football fans in Indonesia. Anarchism is likely to lead to vandalism attitude is very detrimental to yourself or others. Lack of sportsmanship spirit football fans in Indonesia are still frequently encountered, it is necessary for an awareness to change it all. Public service ads are ads that criticize noncommercial purposes, satirical, or invited to do the positive nature of social problems. A public service announcements that are invited will be more easily accepted by the community by giving exposure to social phenomena. Metaphor is a delicate metaphor used to describe something as non-verbal. An advertisement that contains a message and visualized through metaphor will be more impressed solicitation and not patronize them head on. Metaphorical approach used to convey a message, video public service announcements Kick It Out will convey a subtle message.Keywords: supporter, advertising, metaphor, directing